Tactical audio and acoustic rendering in biomedical applications. - Jovanov, E.
Complexity of biomedical data requires novel sophisticated analysis and presentation methods. Sonification is used as a new information display in augmented reality systems to overcome problems of existing human-computer interfaces (e.g., opaque or heavy head-mounted displays, slow computer graphics, etc.). A novel taxonomy of sonification methods and techniques is introduced. We present our experience with tactical audio and acoustic rendering in biomedical applications. Tactical audio as an audio feedback is used as support for precise manual positioning of a surgical instrument in the operating room. Acoustic rendering is applied as an additional information channel and/or warning signal in biomedical signal analysis and data presentation.
Keywords: EEG; Acoustic rendering; Audio feedback; Augmented reality; Biomedical applications; Biomedical signal analysis; Data analysis; Data presentation methods; Human-computer interfaces; Information display; Operating room; Sonification; Surgical instrument; Tactical audio